Application value of oral targeted drug management program led by specialist nurses in continuous nursing for lung cancer patients - Zhang, Xinyu; Lian, Tingting (Frontiers in Medicine, 2025)
ObjectiveOur research attempted to clarify impact of oral targeted drug management program led by specialist nurses on prognosis of non-small cell lung cancer (NSCLC) patients under treatment with oral targeted drugs out of hospital.MethodsNSCLC patients visiting our hospital enrollment as research cohort. The 80 patients received enrollment in our research and division into intervention group and control group through random number table method. The control group underwent conventional nursing. Based on control group, intervention group underwent an oral targeted drug management program led by specialist nurses. Patients received follow-up at 2, 4 and 6 months after discharge.ResultsAt follow-up of 4 and 6 months, incidence of missed medication events in intervention group displayed depletion relative to that in controls. At follow-up of 4 and 6 months, patients’ medication compliance in intervention group displayed elevation relative to that in controls. Incidence of adverse drug reactions displayed depletion in intervention group. At follow-up of 2, 4 and 6 months, incidence of erythra in intervention group displayed depletion relative to that in controls. At follow-up of 6 months, general health, physical functioning and social functioning scores in intervention group displayed elevation relative to those in controls. The scores of above indicators in both groups at follow-up of 6 months displayed elevation relative to those at follow-up of 2 months.ConclusionAn oral targeted drug management program led by specialist nurses can effectively elevate patients’ compliance, reduce incidence of adverse drug reactions and improve patients’ quality of life.